Автоімунний тиреоїдит як позапечінковий прояв вірусного гепатиту В - Голубовська, О. А.; Чепілко, К. І.; Кондратюк, Л. О. (Clinical Endocrinology and Endocrine Surgery, 2010)
Problem of diagnostics of thyroid pathology at the viral hepatitis background is discussed in the article. Clinical case is demonstrated. It is outlined that creation of unified network of giving help to patients with viral hepatitis will be allowed to improve a revelation of infected persons, to provide timely treatment and following-up that can decrease high rates of expansion of hepatitis in our country.